HUBUNGAN SIKAP, MOTIVASI DAN PEMANFAATAN MEDIA BELAJAR DENGAN PRESTASI BELAJAR IPS PADA UPT SDI BENTENG TIMUR NO. 112 KEPULAUAN SELAYAR - Andi Haidir Hidayat; Muhammad Fahreza W (STKIP Pembangunan Indonesia Makassar, 2022)
This study aims to determine 1) whether there is a significant relationship between the implementation of online learning and the psychology of UPT SDN 59 Selayar Islands students 2) how big the relationship between online learning implementation and the UPT SDN 59 Selayar Islands students'psychology.This type of research is quantitative-correlational, which is one type of research designed to determine the degree of relationship between different variables. This research was conducted at UPT SDN 59 Selayar Islands. The population in this study were all students with the number of samples for class VI A, namely 20 people and class VIB, namely 22 people. Data collection techniques used questionnaires and documentation techniques. Data analysis techniques used descriptive analysis and person correlation analysis. The resume showed that I) there was a significant relationship between the implementation of online learning and the psychology of students for both class VI A and class VI B with a moderate category 2) For class VI there was a relationship between the implementation of online learning w'Eh a contribution of 23.6% to student psychology, while for class VI B has a relationship with the implementation of online learning with a contribution of 20. 6% to the psychology of students. Keywords : Online Learning, Student Psychology, Pearson Correlation.